Penyelenggaraan Pelayanan Publik Di Indonesia, Sudahkah Berlandaskan Konsep “Welfare State”? - Nuriyanto, Nuriyanto (Mahkamah Konstitusi Republik Indonesia, 2014)
Preamble to the Constitution of the Republic of Indonesia in 1945 (UUD 1945) mandated that the established goals of the Republic of Indonesia, among others, is to promote the general welfare and to make smart the nation. The mandate implies the duty to meet the needs of all citizens through a system of government that supports the creation of a quality public service in order to meet basic needs and civil rights of every citizen for public goods, public services, and administrative services. Generally indeed the concept of public service as stipulated in Undang- UndangNo. 25 tahun 2009 about Public Service was good enough. It’s just that the implementation is still not ideal, because the good enough concept is not backed up by the threat of punishment appropriate and inappropriate. For example, the authors found in Article 34 is enough to provide the ideal behavior of the implementing rules of profesional public service, but if examined further in Article 54 until 58 a set of sanctions, none of penalty that could be imposed for implementing public service violation of the rules implementing the behavior of public service as stated in the Article 34. So if the executor violated ethical behavior in public service no penalty can be imposed for violations of the ethics of public service.